Liver-Directed AAV8 Booster Vaccine Expressing Plasmodium falciparum Antigen Following Adenovirus Vaccine Priming Elicits Sterile Protection in a Murine Model - Shahnaij, Mohammad; Iyori, Mitsuhiro; Mizukami, Hiroaki; Kajino, Mayu; Yamagoshi, Iroha; Syafira, Intan; Yusuf, Yenni; Fujiwara, Ken; Yamamoto, Daisuke S.; Kato, Hirotomo; Ohno, Nobuhiko; Yoshida, Shigeto (Frontiers in Immunology, 2021)
Hepatocyte infection by malaria sporozoites is a bottleneck in the life-cycle of Plasmodium spp. including P. falciparum, which causes the most lethal form of malaria. Therefore, developing an effective vaccine capable of inducing the strong humoral and cellular immune responses necessary to block the pre-erythrocytic stage has potential to overcome the spatiotemporal hindrances pertaining to parasite biology and hepatic microanatomy. We recently showed that when combined with a human adenovirus type 5 (AdHu5)-priming vaccine, adeno-associated virus serotype 1 (AAV1) is a potent booster malaria vaccine vector capable of inducing strong and long-lasting protective immune responses in a rodent malaria model. Here, we evaluated the protective efficacy of a hepatotropic virus, adeno-associated virus serotype 8 (AAV8), as a booster vector because it can deliver a transgene potently and rapidly to the liver, the organ malaria sporozoites initially infect and multiply in following sporozoite injection by the bite of an infected mosquito. We first generated an AAV8-vectored vaccine expressing P. falciparum circumsporozoite protein (PfCSP). Intravenous (i.v.) administration of AAV8-PfCSP to mice initially primed with AdHu5-PfCSP resulted in a hepatocyte transduction rate ~2.5 times above that seen with intramuscular (i.m.) administration. This immunization regimen provided a better protection rate (100% sterile protection) than that of the i.m. AdHu5-prime/i.m. AAV8-boost regimen (60%, p < 0.05), i.m. AdHu5-prime/i.v. AAV1-boost (78%), or i.m. AdHu5-prime/i.m. AAV1-boost (80%) against challenge with transgenic PfCSP-expressing P. berghei sporozoites. Compared with the i.m. AdHu5-prime/i.v. AAV1-boost regimen, three other regimens induced higher levels of PfCSP-specific humoral immune responses. Importantly, a single i.v. dose of AAV8-PfCSP recruited CD8+ T cells, especially resident memory CD8+ T cells, in the liver. These data suggest that boost with i.v. AAV8-PfCSP can improve humoral and cellular immune responses in BALB/c mice. Therefore, this regimen holds great promise as a next-generation platform for the development of an effective malaria vaccine.